BIOFILMS AS A PHENOMENON IN THE SUGAR INDUSTRY - Заславський, Александр; Станиславив, Светлана; Шейко, Тамила (Modern engineering and innovative technologies, 2022)
The problem of microbiological biofilm formation in the process of obtaining diffusion juice in the sugar industry is considered in detail. Its structure and main components, transformations and characteristics. Described in the types of contaminating mi